The relationship between psychological resilience and perceived stress in adults: The mediating role of general self efficacy [Yetişkinlerde psikolojik sağlamlık ile algılanan stres arasındaki İlişki: Genel öz yeterliğin aracı rolü] - (:unkn) unknown (Turkish Psychological Counseling and Guidance Association, 2021)
In this study, it was aimed to examine the mediating role of general self efficacy in the relationship between psychological resilience and perceived stress of adult individuals. The participants of the study are 634 people, 362 women and 272 men, aged between 18 and 72. SPSS PROCESS macro plug-in was used to test the hypotheses using the data collected in the research and conditional process analysis was performed. Apart from this, the significance of the mediator variable was made using the bootstrapping method, which is considered a more modern approach today. First, Pearson product-moment correlation coefficient was calculated to determine the relationship between variables, and it was found that there were significant relationships between psychological resilience, both with perceived stress and general self efficacy. In addition, a significant relationship was found between perceived stress and general self efficacy. General self efficacy was found to have a significant partial mediating role in the relationship between psychological resilience and perceived stress. The fact that the mediating role of general self efficacy in the relationship between psychological resilience and perceived stress has not been examined in the literature is considered important for this study. All the findings obtained in this direction were discussed with similar studies in the light of the literature and some suggestions were made. © Common Ground Research Networks, Lindsay Asquith, Sumati Ahuja, All Rights Reserved.